Commission of the European Communities v. Microsoft Corporation : summary of decision of The Court of First Instance - Bagley, Constance E., (SAGE knowledge. Cases., 2016)
On December 10, 1998, Sun Microsystems lodged a complaint with the European Commission relating to Microsoft Corporation's refusal to give Sun the information and technology necessary to allow its work group server operating systems to interoperate effectively with the Windows client PC operating system. Thereafter, the Commission, acting on its own initiative, launched an investigation relating to (1) Microsoft's Windows 2000 generation of client PC and work group server operating systems and (2) the integration by Microsoft of its Windows Media Player in its Windows client PC operating system. This case study examines this topic.